Great expectations : what kids want from our urban public schools - Caruthers, Loyce Ellenor, 1947-; Friend, Jennifer Ingrid (Emerald Publishing Limited : Information Age Publishing, Inc., 2016)
This book explores meaningful and effective use of student voice in urban school renewal efforts through strategies that include: surveys, interviews, focus groups, visual and video projects, social media, and student participation in governance. Chapters provide a definition of student voice, context for public schooling in the United States, and introduce a framework for including student voice in school renewal processes. Examples guide readers to implementation of the framework to include student voices in diverse educational settings. Authentic voices of approximately 175 students interviewed by the authors express what it is that they really want from public schools and how pre K-12 educators can provide a structure for ongoing student participation in governance and the work of the school. The existing literature explores student characteristics such as poverty, cultural diversity, and what the experts believe students need public schools to provide. Within the research, urban public schools and technical reform are often explored and examined separately from conversations about what students want from schools, excluding opportunities for their voices and diverse perspectives to be heard. Listening to students describe instances of bullying or teachers' low academic expectations provides educators with opportunities to address issues that impede student learning. The uniqueness of this framework for including student voice is that it provides multiple opportunities for students in any grade level to tell us what it is they want from public schools, and to make meaningful and lasting contributions to school renewal efforts.